The Relationship between Materialistic Aspirations and Distinct Aspects of Psychological Well-being in a UK sample - Parker Natasha; Ivtzan Itai (Journal of Behavior Therapy And Mental Health, 2016)
The purpose of this research is to gain a deeper understanding of how materialistic aspirations are related to distinct aspects of psychological well-being. Research has consistently found a negative relationship between materialistic goals and well-being, but a review of the literature identified that the measures of well-being used in the majority of studies were measures of what Keyes 1 describes as “subjective well-being” or “hedonic happiness”. Criticisms of these types of measures are that they fixate too much on the momentary experience of pleasure and don’t take into account what is meaningful and or what contributes to long lasting fulfilment. Very little research was found investigating the impact of materialism on “eudaimonic” well-being, which is found through doing what is worthwhile and realising ones potential and has been found to have a longer lasting impact on overall well-being 2. To address this gap in the literature, a convenience sample of 113 adult subjects in the UK were recruited through Facebook and asked to respond to the Aspiration Index and the Psychological wellbeing scale. The relative importance placed on extrinsic (materialistic) and intrinsic aspirations was compared to the six dimensions of psychological well-being. In line with previous research, higher importance placed on materialistic aspirations for wealth, status and image were found to be negatively correlated with all aspects of psychological well-being. However, the strongest and only statistically significant negative correlation was between extrinsic aspirations and positive relations with others (r = -.256, p< 0.01). Positive relationships with other people form a central component of many theories of well-being and so this negative relationship may help to explain why materialistic aspirations are so consistently found to be negatively correlated to a variety of measures of well-being. Further research is needed to explore this relationship as no causation could be inferred.
Keywords: Materialism